Effect of cluster set warm-up configurations on sprint performance in collegiate male soccer players - Nickerson, B. S.; Mangine, G. T.; Williams, T. D.; Martinez, I. A. (Applied Physiology, Nutrition, and Metabolism, 2018)
The purpose of this study was to determine if back squat cluster sets (CS) with varying inter-repetition rest periods would potentiate greater sprint performance compared with a traditional set parallel back squat in collegiate soccer players. Twelve collegiate male soccer players (age, 21.0 ± 2.0 years; height, 180.0 ± 9.0 cm; body mass, 79.0 ± 9.5 kg) performed a 20-m sprint prior to a potentiation complex and at 1, 4, 7, and 10 min postexercise on 3 separate, randomized occasions. On each occasion, the potentiation complex consisted of 1 set of 3 repetitions at 85% 1-repetition maximum (1RM) for the traditional parallel back squat. However, on 1 occasion the 3-repetition set was performed in a traditional manner (i.e., continuously), whereas on the other 2 occasions, 30s (CS30) and 60 s (CS60) of rest were allotted between each repetition. Repeated-measures ANOVA revealed greater (p = 0.022) mean barbell velocity on CS60 compared with the traditional set. However, faster (p < 0.040) 20-m sprint times were observed for CS30 (3.15 ± 0.16 s) compared with traditional (3.20 ± 0.17 s) only at 10 min postexercise. No other differences were observed. These data suggest that a single cluster set of 3 repetitions with 30-s inter-repetition rest periods at 85% 1RM acutely improves 20-m sprinting performance. Strength and conditioning professionals and their athletes might consider its inclusion during the specific warm-up to acutely improve athletic performance during the onset (=10 min) of training or competition.